Generation, mixing and alteration of thermogenic and microbial gas in oil deposits: The case of the Alpine Foreland Basin (Austria). (December 2016) - Pytlak, L.; Gross, D.; Sachsenhofer, R.F.; Bechtel, A.; Gratzer, R.; Linzer, H.-G.
Abstract: Molecular and stable isotope compositions were determined for forty eight gas samples taken from wells producing oil form Cretaceous and Eocene reservoirs. Gas was expelled from source rock at various maturity levels (0.6–1.2%Rr). Gas maturities based on stable carbon isotopes are in general agreement with those found in oils. Nevertheless, results revealed that most fields trap methane derived from a source which is not thermogenic. Shallow northeastern reservoirs trap methane interpreted as secondary microbial in origin. The same process is proposed here as source of methane in western deposits. Moreover, those gases are enriched in 2 H isotope suggesting different methanogenesis pathways. Fields along the southern margin of the Alpine Foreland Basin where reservoir temperature exceeds 80 °C host methane generated during primary organic matter degradation. Thus, Eocene and Lower Oligocene layers should be considered as potential source rocks. This study gives new insight to filling history of traps and revealed a more complicated geological background and hydrocarbons generation than have been assumed until now. Highlights: Methane associated with oil in Austrian part of Alpine Foreland Basin is an mixture of thermogenic and biogenic. Microbial methane is primary and secondary in origin. Gas maturities are in agreement with oil maturities. New potential source rock for primary microbial methane is proposed. New aspect of trap charging history is suggested.